British Diplomatic and Military Preparations for the Pacific War from 17 October to 7 December 1941 - Mordzak, Adam (Before the Battle, 2023)
The assumption of the post of Prime Minister of Japan by General Tojo Hideki on 17 October 1941 was interpreted in London as a prelude to further aggressive actions on the part of Tokyo. The purpose of this article is to examine what steps the British government took to prepare for a potential confrontation in diplomatic and military fields. A key reinforcement of British forces was the creation of the Far East Fleet squadron intended to serve as a primary deterrent, which was done at the expense of weakening the position of the British Navy in other areas. In contrast, land troops in the Malay region received only token support. The Air Force was in the worst position, as there were far too few aircraft for defensive purposes and they were not of the best quality. However, due to the involvement on other fronts and supplying military equipment to the Soviet Union, it was impossible to deliver more weapons to Southeast Asia. In the area of diplomacy, the main effort was directed at securing guarantees of support from the United States. However, due to the Neutrality Acts and the general reluctance of the American public to participate in the war, only verbal promises of assistance were obtained. Cooperation with the Dutch East Indies authorities went much better and they remained the most important ally for the British Empire in the area. In addition, attempts were made to enlist the cooperation of Thailand, but London’s offer to that country remained extremely unattractive, as the British were unable to provide guarantees of territorial integrity for the Thais. All these factors, combined with a misreading of Japanese intentions, meant that Britain entered the armed conflict with Japan poorly prepared, leading to the defeat at the Battle of Malaya and the fall of Singapore